MENINGKATKAN KREATIVITAS BELAJAR SISWA DENGAN MENGGUNAKAN METODE KARYAWISATA PADA MATA PELAJARAN BAHASA INDONESIA POKOK BAHASAN MENULIS KARANGAN BEBAS KELAS III SDN 2 METRO BARAT KOTA METRO T.P 2010/2011 - sunarti sunarti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
Skills, abilities and professionalism of teachers are highly demanded at this time, therefore, a teacher must be able to choose and use the tools or methods appropriate teaching so that learning materials can be presented in accordance with the expected goals. The formulation of this thesis is whether the problem by using a field method can enhance the creativity of students learning Indonesian subjects the subject of free essay writing class III SDN 2 Metro West Metro Academic Year 2010/2011. Improving student learning creativity of a teacher should be able to know and be able to find strategies or methods that are thought to increase the creativity of student learning. As one of the methods that can be used for learning is a field method, since the use of this method is fun and can eliminate boredom. The goal of this research is the third grade students of SDN 2 Metro West Metro City. The results obtained are using a field method can enhance creativity Indonesian learning materials free Siwa essay writing class III in teaching and learning in the classroom in terms of the percentage increase in student learning hasi start cycle I and II. Keywords: Creativity learn some vital lessons, Method Leisure